Breaking The Resistance: Bacteriophage "Novel" Pisf-Ab082 As An Alternative Treatment For Multidrug Resistant A. Baumannii - Mustufa, Mustufa; Mohamad Yapanto, Alvian (Journal of Comprehensive Science, 2023)
Acinetobacter baumannii is a gram-negative, non-motile bacterium that causes infections, particularly in wounds and burns. MDR A. baumannii strains are resistant to multiple types of antimicrobials, making them difficult to treat. Phage therapy is a potential strategy to combat MDR A. baumannii infections, as bacteriophages can specifically target and kill bacterial cells without harming human cells. This study aims to review the efficacy of bacteriophages as an alternative treatment for MDR A. baumannii and explore their synthesis methods. The article presents a method for isolating and purifying bacteriophages from waste samples using MDR A. baumannii as an indicator. Bacteriophage therapy has no detectable side effects and can reduce the impact on human gut microflora compared to antibiotics. However, more clinical research is needed to establish the safety and effectiveness of using bacteriophages as an antibiotic-resistant therapy. In conclusion, bacteriophages have the potential to become a therapeutic agent to control nosocomial infections caused by MDR A. baumannii. The specificity of bacteriophages for the infected pathogen reduces their impact on human gut microflora compared to antibiotics. However, more research is required to establish the safety and effectiveness of bacteriophages as an antibiotic-resistant therapy, including studies on potential side effects and administration methods. Overall, this study highlights the potential of bacteriophages as an alternative to antibiotics and the need for further research in this area